Pengalaman Emosi dan Mekanisme Koping Lansia yang Mengalami Penyakit Kronis - - Suyanta; Endang Ekowarni (Jurnal Psikologi, 2012)
The process of aging is a natural process faced by humans. They may experience health problems when it gets old, it is contributing to their emotional suffering. This study aims to answer the question of how the experience of seniors during chronic disease, what is the meaning of old age and disease for the elderly, how the dynamics of the elderly in the face of chronic illness , and what are the factors that influence the experience of emotions and coping mechanisms elderly who have chronic diseases. The study was conducted with a qualitative phenomenological approach, involving 6 subjects as key informants , and 6 family members and community leaders as one additional informant. The data was collected through in-depth interviews and participatory observation. Subject selection is determined by reference to key person who know the condition of the subject to the criteria of age 60 years or older , had more chronic disease than a year, can provide information through interviews. Results showed that the elderly experience while facing chronic illness can be identified through the important themes that are synthesized in the form of the internal dimensions of the disease view of the subject , the denial of the disease, the emergence of the thoughts that accompany illness, the emergence of a variety of emotional experience, surrender to face pain, and actions undertaken in overcoming the disease, and the external dimension of support or attention of the family. Old age is interpreted as the age of the subjects was nearing death, a lot of pain, and the patient should be approached religion, and should be able to accept the situation. Disease is defined as fairness occurs in old age, as a rebuke of God, as a trial, as a reward, as a disaster, as well as the will of God. Thoughts that accompany the disease appears to make the subject was not ready to accept the disease in old age. Old age is the age of the end of life and disease is the cause of a person's death. Factors that influence the experience of emotions and coping mechanisms include lack of knowledge about the subject of illness, type of illness and prior illness experiences, desires and thoughts experienced by subjects when sick, and the presence or absence of support or care from family for sick. Keywords: chronic disease, coping, elderly, emotion